Unfavorable iliac artery anatomy causing access limitations during endovascular abdominal aortic aneurysm repair: application of the endoconduit technique - Jaldin, Rodrigo Gibin [UNESP]; Sobreira, Marcone Lima [UNESP]; Moura, Regina [UNESP]; Bertanha, Matheus [UNESP]; Mariaúba, Jamil Víctor de Oliveira [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; Yoshida, Ricardo de Alvarenga [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2014)
Endovascular aneurysm repair (EVAR) is already considered the first choice treatment for abdominal aortic aneurysms (AAA). Several different strategies have been used to address limitations to arterial access caused by unfavorable iliac artery anatomy. The aim of this report is to illustrate the advantages and limitations of each option and present the results of using the internal endoconduit technique and the difficulties involved.

O tratamento endovascular para aneurisma de aorta abdominal (AAA) já está bastante difundido, sendo considerado como primeira escolha na maioria dos casos. Limitações no acesso pelas artérias ilíacas tortuosas, com estenoses, calibre pequeno ou doença oclusiva já foram contornadas com o uso de condutos, dissecção direta aortoilíaca, angioplastias, entre outros procedimentos. O objetivo deste desafio é mostrar as vantagens e limitações de cada alternativa, além de apresentar o resultado e as dificuldades com o endoconduíte.
Tratamento endovascular do aneurisma de aorta abdominal associado à dificuldade no acesso aórtico devido a artérias ilíacas de pequeno calibre: aplicação técnica do Endoconduíte
Keywords: Aortic aneurysm; Endovascular procedures; Surgical procedures; Minimally invasive; Iliac artery; Vascular access devices; Aneurisma aórtico; Procedimentos endovasculares; Procedimentos cirúrgicos minimamente invasivos; Artéria ilíaca; Dispositivos de acesso vascular